The Influence Of Placement, Development Of Human Resources And Infrastructure On The Implementation Of Asn Department's Duties For Women's Empowerment, Child Protection, Population And Family Control District Planning Selayar Islands - Andi Irmayani; Muhammad Rusydi; Edi Jusriadi (Green Publisher Indonesia, 2024)
The Influence of Placement, Development of Human Resources and Infrastructure on the Implementation of ASN's Duties and Duties of the Women's Empowerment, Child Protection, Population Control and Family Planning Services of Selayar Islands Regency, guided by Mr. Muhammad Rusydi as supervisor I and Mr. Edi Jusriadi as supervisor II. This research aims to analyze and understand the influence of placement on the implementation of ASN's main duties and functions, development of human resources on the implementation of ASN's main duties and functions, and infrastructure on the implementation of ASN's main duties and functions at the Department of Women's Empowerment, Child Protection, Population Control and Family Planning, Selayar Islands Regency. This type of research is quantitative with a sample of 55 respondents using a questionnaire as a source of data collection. The analysis used is Multiple Linear Regression Analysis using the SPSS V.29 application. The research results show that: (1). Placement has a positive and significant effect on the implementation of ASN's main duties and functions, (2). Human resource development has a positive and significant effect on the implementation of ASN's main duties and functions, and (3). Infrastructure has a positive but not significant effect on the implementation of ASN's main duties and functions at the Women's Empowerment, Child Protection, Population Control and Family Planning Services in Selayar Islands Regency.